POWSTANIE, ROZWÓJ I UPADEK KOMANDORII TEMPLARIUSZY W CHWARSZCZANACH - Wasilkiewicz, Kamil (In Gremium. Studies in History, Culture and Politics, 2011)
THE ESTABLISHMENT, THE DEVELOPMENT, AND THE FALL OF THE TEMPLAR COMMANDERY IN CHWARSZCZANY The Templars came to Poland in the 13’h century on the initiative of the rivaling princes: Henry I the Bearded, Władysław Odonic and Barnim I. Thanks to the protection of these rulers, the order created 8 commanderies in the Pomerania, in Ziemia Lubuska, Great Poland and in Silesia. They were placed in Oleśnic a Mała, Wielowieś, Chwarszczany, Leśnica, Czaplinka, Wałcz, Rurka and Myśliborz. Chwarszczany was the headquarters of the Polish Templars. This article shows the history of this commandery from the moment of its founding in the l230s until the last moments of its functioning at the beginning of the 14th century.